2013
DOI: 10.3109/10428194.2013.779691
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total body irradiation plus cyclophosphamide with busulfan plus cyclophosphamide as conditioning regimens in patients with acute lymphoblastic leukemia undergoing allogeneic hematopoietic stem cell transplant

Abstract: Conditioning regimens used during stem cell transplant provide prolonged control or cure of the disease in patients with acute lymphoblastic leukemia (ALL). In this study, we present a comparison of treatment results for 95 patients with ALL who underwent allogeneic hematopoietic stem cell transplant (AHSCT) with total body irradiation plus cyclophosphamide (TBI + Cy) or busulfan plus cyclophosphamide (Bu + Cy) as conditioning regimen. Median age was 25 (range: 9-54) years. Median follow-up was 24 (range: 3-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
4
27
2
Order By: Relevance
“…Although comparison of TBI with myeloblative chemotherapy in a setting of ALL has never been a subject of a prospective trial, some retrospective analyses confirmed the advantage of TBI. 17,18 Results of the current study strongly support this statement. New, irradiationfree regimens based on the use of thiotepa are under development; however, their utility requires further evaluation.…”
supporting
confidence: 79%
“…Although comparison of TBI with myeloblative chemotherapy in a setting of ALL has never been a subject of a prospective trial, some retrospective analyses confirmed the advantage of TBI. 17,18 Results of the current study strongly support this statement. New, irradiationfree regimens based on the use of thiotepa are under development; however, their utility requires further evaluation.…”
supporting
confidence: 79%
“…24,25 In pediatric or adult ALL, a better outcome has been described for TBI-based regimens compared with chemotherapy-based regimen such as oral Bu-Cy. 23,[26][27][28] Meanwhile, the improved results with TBI may result from the variable pharmacokinetics reported for oral Bu and/or the increased NRM reported for oral Bu-Cy. 23,27 As IV Bu has progressively replaced oral Bu in the past decade, these unspecific ALL data may not apply in the IV Bu era or in the specific T-ALL disease.…”
Section: Discussionmentioning
confidence: 99%
“…Median EFS was 4 months in the Bu and Cy arm, while it was 13 months in the TBI and Cy arm indicating that TBI and Cy conditioning regimes to be superior to the Bu and Cy regime. 12 The larger cohort of patients within this study indicates a higher degree of certainty, but there were some flaws within the methodology such as a lack of randomisation and omission in the data of the patients' remission statuses. The median age of participants was 25 years making it hard to draw direct comparison with other studies, but was deemed worthy of inclusion within this discussion as the ages ranged from 9 years old.…”
Section: Tbi V Chemotherapymentioning
confidence: 97%
“…A larger trial with 95 participants conducted by Eroglu et al (2013) carried out a direct comparison of Bu and Cy versus TBI and Cy as a conditioning regime for ALL. Median EFS was 4 months in the Bu and Cy arm, while it was 13 months in the TBI and Cy arm indicating that TBI and Cy conditioning regimes to be superior to the Bu and Cy regime.…”
Section: Tbi V Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation